Study of English Language Teaching in Higher Vocational Schools in Thailand: A Case Study of English Language Teaching in Higher Vocational Schools in Chiang Rai Province - Yomyao, Adisak; Khammun, Mongkol (Journal of Advanced Development in Engineering and Science, 2023)
The aim of this research is to study the current status including various problems and obstacles in English language learning and teaching for business administration division in higher vocational schools in Chiang Rai Province. Its population samples were 15 of English teachers in various vocational schools in Chiang Rai Province and 229 of the first year higher vocational students and 267 of the second year higher vocational students in business administration division from the main vocational schools in Chiang Rai. Data were distributed and collected by using questionnaire for teachers and tests for students. Percentage, mean and standard deviation were calculated for analyzing the data in order to get its findings.